Multimodality Analysis In The Movie "Turning Red" With A Semiotic Approach - Faisal Zachrie; Maisa Maisa; Haris Budiana; Siti Fatimah Nurjanah; Ariq Nurfauzan (International Journal of Multilingual Education and Applied Linguistics, 2024)
Film is one of the media to communicate to the audience. The film "Turning Red" shows a picture of how parenting can affect the growth and development of children, this film also features elements of Chinese culture. The film "Turning Red" is interesting to study because it has moral values that can be a reflection for parents in educating children. Researchers want to see the relationship between signs and objects to explain the representation of Chinese culture and the influence of parenting on child development through gestures, expressions, and colors, on the characters Mei and Ming in the film "Turning Red". The qualitative research method to analyze multimodality in the film "Turning Red" with a semiotic approach is done by understanding the signs contained in various modes of expression such as visual, language, music, and sound. Multimodal analysis with this semiotic approach can involve understanding how color, music, and language are used to convey cultural and emotional messages in the film, and how all these elements interact to create a deep and meaningful audience experience.